Digital Unwrapping of the Mummy of King Amenhotep I (1525–1504 BC) Using CT - Saleem, Sahar N.; Hawass, Zahi (Frontiers in Medicine, 2021)
The mummy of King Amenhotep I (18th Dynasty c.1525-1504 BC) was reburied by the 21st Dynasty priests at Deir el-Bahari Royal Cache. In 1881 the mummy was found fully wrapped and was one of few royal mummies who have not been unwrapped in modern times. We hypothesized that non-invasive digital unwrapping using Computed Tomography (CT) would provide insights on the physical appearance, health, cause of death and mummification style of the mummy of King Amenhotep I. We examined the mummy with CT and generated two- and three-dimensional images for the head mask, bandages, and the virtually unwrapped mummy. CT enabled visualization of the face of Amenhotep I who died around the age of 35 years. The teeth had minimal attrition. There was no CT evidence of pathological changes or cause of death. The body has been eviscerated via a vertical left flank incision. The heart is seen in the left hemithorax with an overlying amulet. The brain has not been removed. The mummy has 30 amulets/jewelry pieces including a beaded metallic (likely gold) girdle. The mummy suffered from multiple postmortem injuries likely inflicted by the tomb robbers that have been likely treated by 21st Dynasty embalmers. These included fixing the detached head and neck to the body with a resin-treated linen band; covering a defect in the anterior abdominal wall with a band and placing two amulets beneath; placement of the detached left upper limb beside the body and wrapping it to the body. The transversely oriented right forearm is individually wrapped likely representing the original 18th Dynasty mummification and considered the first known New Kingdom mummy with crossed arm at the chest. The head mask is made of cartonnage and has inlaid stone eyes. Digital unwrapping of the mummy of Amenhotep I using CT sets a unique opportunity to reveal non-invasively the physical features of the King, understand the mummification style early in the 18th Dynasty, and the reburial intervention style by 21st Dynasty embalmers. This study may make us re-confidence in the goodwill of the Royal mummies’ reburial project by the 21st Dynasty priests.